Involvement of the recB-recC Nuclease (Exonuclease V) in the Process of X-Ray-Induced Deoxyribonucleic Acid Degradation in Radiosensitive Strains of Escherichia coli K-12 - Youngs, David A. (1973)
The ras, polA, exrA, recA, and uvrD3 strains of Escherichia coli K-12 degrade their deoxyribonucleic acid more extensively than wild-type strains after X irradiation. The relationship of the recB-recC nuclease (exonuclease V) to the degradation process in these strains was determined by comparing the degradation response of the original strains with that of strains containing an additional recB21 or recC22 mutation. The initial rate of degradation in ras, polA12, exrA, and recA13 strains after an exposure of 20 to 30 kR was reduced more than 10-fold by the presence of an additional recB21 or recC22 mutation. The extent of degradation in these irradiated strains after 90 to 120 min of incubation was reduced two- to fivefold. In the uvrD3 strain, a recC22 mutation caused a fourfold decrease in initial degradation rate and reduced the extent of degradation after 90 min of incubation by a factor of 1.6. The results are consistent with the statement that the degradation process is normally dependent on exonuclease V activity. However, the observation that 10 to 30% degradation always occurred even in recB or recC strains, which lack this enzyme, suggests that alternative degradation mechanisms exist.